Pembatalan Merek Terdaftar Yang Memiliki Persamaan Nama Pada Pokoknya - Yehuda Goodlife Nusale; Teng Berlianty; Theresia Louize Pesulima (PATTIMURA Law Study Review, 2023)
ABSTRACT: According to Law Number 20 of 2016 Concerning Trademarks and Geographical Indications, Article 21 Paragraph 1 Letters a and c Concerning Trademark Registration Procedures which explains that the application for trademark registration is rejected if the registered trademark belongs to another party or is applied for beforehand by another party for similar goods and/or services and has no distinguishing power, but in practice there are registered brands that have the same name in essence, namely the "GOTO" brand which has similarities in writing and pronunciation. The law related to the problem is then linked to secondary legal material through books, articles, journals or writings by legal experts, after which it is connected with legal facts, legal events and legal consequences which are carried out using the Statute Approach and the Conceptual Approach. The research results show: 1). The trademark rights holder is the first party to register the mark with the Directorate General of Intellectual Property Rights, and the holder of the rights to this mark receives legal protection, if another party registers the same mark, it has violated the system adopted by the law, namely the first to file principle and also violates the law itself as the accommodator of all regulations regarding trademark registration 2). Settlement of the Goto case as an effort to resolve the similarity in the mark at registration, legal action through a lawsuit in a commercial court as a legal remedy if it is proven to legally use the mark without permission.